2013
DOI: 10.1007/s00120-013-3135-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolisches Syndrom und Prostatakarzinom

Abstract: The relationship between metabolic syndrome (MS) and prostate cancer (PCA) is highly complex and harbors multiple facets not least because MS is not a single entity but represents a poorly defined inhomogeneous mixture of different diseases and conditions. Although numerous studies suggest a correlation between MS or components of MS and the development of prostate cancer, current evidence cannot be considered convincing. While diabetes appears to be inversely related to PCA, increased serum levels of triglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies on keratin 8 have shown that it is an essential member of the keratin family, which plays an important role in glucose metabolism [9,11]. Although problems with the uptake of glucose and its metabolites in hepatocytes are mainly attributed to chronic insulin-related disease, there is also evidence supporting a correlation between diabetes and various malignant tumors [12][13][14][15]. A similar correlation exists between glycogen storage disease and liver cell abnormality.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on keratin 8 have shown that it is an essential member of the keratin family, which plays an important role in glucose metabolism [9,11]. Although problems with the uptake of glucose and its metabolites in hepatocytes are mainly attributed to chronic insulin-related disease, there is also evidence supporting a correlation between diabetes and various malignant tumors [12][13][14][15]. A similar correlation exists between glycogen storage disease and liver cell abnormality.…”
Section: Introductionmentioning
confidence: 97%
“…Non-interventional study on effectiveness and tolerability and on the influence of anamnestic factors”) is an open-label, multi-centre, non-interventional German cohort study of Leuprone HEXAL in routine clinical practice. This study was designed to extend existing knowledge on the efficacy and tolerability of leuprorelin solid implant in men with PCa and to explore the influence of patient and lifestyle factors on disease course [4, 7-9]. This manuscript also compares the real-world clinical use for LHRH agonists in a contemporary patient cohort with guideline-recommended indications.…”
Section: Introductionmentioning
confidence: 99%